2014
DOI: 10.1093/molbev/msu296
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Polyploidy Events in the Early Radiation of Nodulating and Nonnodulating Legumes

Abstract: Unresolved questions about evolution of the large and diverse legume family include the timing of polyploidy (whole-genome duplication; WGDs) relative to the origin of the major lineages within the Fabaceae and to the origin of symbiotic nitrogen fixation. Previous work has established that a WGD affects most lineages in the Papilionoideae and occurred sometime after the divergence of the papilionoid and mimosoid clades, but the exact timing has been unknown. The history of WGD has also not been established fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
216
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 208 publications
(240 citation statements)
references
References 58 publications
(104 reference statements)
17
216
3
Order By: Relevance
“…As we confirmed the ploidy level of the sequenced individuals to diploid, we assume that the rather high level of putative paralogy observed in this study comes from a high level of repeated sequences in the genome of R. pseudoacacia . This hypothesis is congruent with the ancestral whole genome duplication events which occurred within the Fabaceae (Cannon et al., ; Soltis et al., ). However, it may also be influenced by the fact that we considered all types of paralogous RAD loci, whereas we tested only considered those loci identified by reads 2 snp as true paralogs (“para”).…”
Section: Discussionsupporting
confidence: 80%
“…As we confirmed the ploidy level of the sequenced individuals to diploid, we assume that the rather high level of putative paralogy observed in this study comes from a high level of repeated sequences in the genome of R. pseudoacacia . This hypothesis is congruent with the ancestral whole genome duplication events which occurred within the Fabaceae (Cannon et al., ; Soltis et al., ). However, it may also be influenced by the fact that we considered all types of paralogous RAD loci, whereas we tested only considered those loci identified by reads 2 snp as true paralogs (“para”).…”
Section: Discussionsupporting
confidence: 80%
“…By duplicating genes or whole genomes, redundant copies of key genes regulating the symbiosis can be created (92,93). Because mutations are less likely to disrupt key symbiosis genes, duplication could result in a lower rate of symbiosis loss and higher retention of symbiotic capacity (36,94). The potential link between symbiosis persistence and gene duplication is an interesting research avenue.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in accordance with what was already described for these species. Indeed, it was found that soybean contains a very large number of retained genes from this WGD (Cannon et al, 2015). Additionally, recent studies on large gene families in G. raimondii indicate that their copy number is driven either by retention after the last WGD (e.g.…”
Section: Subgroup-and Species-specific Expansionsmentioning
confidence: 99%